INNOVATIVE CRITERIA AND LEVELS OF DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF FUTURE SPECIALISTS IN THE FIELD OF INFORMATION TECHNOLOGY (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the fact that the development of professional competence of future IT specialists is one of the main conditions for an innovative educational environment, as well as its criteria and levels.